A taxonomic study of Asian soldier beetles of the tribe Malthinini (Coleoptera, Cantharidae, Malthininae), with description of a new genus and a new species of Malthinellus, and notes on the genera Malthinus and Mimomalthinus - Nakamura, Ryo (Zootaxa, 2026)
The malthinine fauna of Asia is highly diverse, but comprehensive studies are lacking, and many species have not been re-examined since their original descriptions. This study mainly focuses on the genus Malthinellus Kiesenwetter, 1874, which comprises ten Asian species. A new species, Malthinellus mushanus sp. nov. is described from Taiwan (Nantou County) and compared with two known Taiwanese species from the same genus, M. crenulatus (Wittmer, 1979) and M. crenulatomimus (Wittmer, 1984). Aedeagus of Malthinellus chinensis Wittmer, 1956 (China) is illustrated and described for the first time. Malthinellus hoabinensis (Wittmer, 1995) comb. nov. (Vietnam) and Malthinellus multispinosus (Wittmer, 1995) comb. nov. (China) are transferred from the genus Malthinus. Malthinellus malickyi Wittmer, 1997 (Thailand) is transferred to a new genus Phaneromalthinus gen. nov. (type species: P. malickyi (Wittmer, 1997) comb. nov.). Additionally, illustrations and notes are provided for several species of the genera Malthinus and Mimomalthinus that resemble Malthinellus. The lectotypes of Malthinus tonkineus Pic, 1923 and Mimomalthinus niger Pic, 1931 are designated and illustrated. The generic definition of Malthinellus is revised, and the differences from Malthinus and Mimomalthinus are discussed.